Some remarks for the History of Public Relations in Portugal - Eiró-Gomes, Mafalda (2016)
Public Relations is considered, especially by its critics, as a very powerful industry, capable of really improving the freedom of citizens but also a possible influence for misguiding and spinning. This seems to be the major problem for the institutionalisation of the profession in Portugal, at least, it has been for the last fifty years where advances and setbacks have been constant. To be able to override its detractors both practitioners and academicians felt the need to offer a definition that would enable a clear distinction from advertising or propaganda, the main professional areas in the first half of the 20th century in Portugal. But this seems a never-ending struggle as nowadays more or less the same problems are faced concerning the so-called ‘content marketing’ areas. Moreover, the ambiguity of the expression ‘public relations’ in the Portuguese language has often helped to create all sort of misunderstandings. As for its place as an academic subject, the way has been a bit easier but the future might be disappointing due to important misconceptions that tend to present the discipline as a sub-discipline of the marketing.